2018
DOI: 10.1097/md.0000000000012262
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of correlationship between HLA-G 3′UTR 14-bp Ins/Del polymorphism and virus susceptibility

Abstract: Background:There is a considerable amount of literature on the potential relationship between human leukocyte antigen-G 14-bp Ins/Del polymorphism and virus infection; however, results from these studies were inconclusive.Objectives:A meta-analysis was carried out to determine whether the 14-bp Ins/Del polymorphism is a susceptible factor for virus infection.Methods:Data were extracted from PubMed and Web of Science databases, and included 10 case–control studies (1835 patients and 2357 controls).Results:A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Some investigator groups have linked this polymorphism with human cytomegalovirus and human T-lymphotropic virus type-1 (HTLV-1) infections [27] , [44] , while others indicated no clear association with viral infections [25] , [45] . However, a meta-analysis study of 10 studies revealed that the overall analysis favored no association between different viral infections and the 14-bp Ins/Del polymorphism, but subgroup analysis demonstrated a significant association with HTLV-1 infection [46] . An additional study has demonstrated that HLΑ-G 14-bp Ins/Del polymorphism was significantly linked to chronic hepatitis B virus in Brazilians [26] .…”
Section: Discussionmentioning
confidence: 98%
“…Some investigator groups have linked this polymorphism with human cytomegalovirus and human T-lymphotropic virus type-1 (HTLV-1) infections [27] , [44] , while others indicated no clear association with viral infections [25] , [45] . However, a meta-analysis study of 10 studies revealed that the overall analysis favored no association between different viral infections and the 14-bp Ins/Del polymorphism, but subgroup analysis demonstrated a significant association with HTLV-1 infection [46] . An additional study has demonstrated that HLΑ-G 14-bp Ins/Del polymorphism was significantly linked to chronic hepatitis B virus in Brazilians [26] .…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the 14‐bp DEL allele and INS/DEL genotype were more frequent in control group than in CHB patients (Eskandari et al, 2017). Yet, not all published results readily support the association between HLA‐G alleles and virus infection susceptibility and several reports (including meta‐analysis) question this linkage (Alves et al., 2015; Lv et al, 2018).…”
Section: Hla‐g and Diseasementioning
confidence: 99%
“…On the other hand, in a meta-analysis study, Lv et al (2018) demonstrated that HLA-G 14-bp Ins/Del polymorphisms may exert no influence on susceptibility to viruses. However, they added that, due to the limited number of studies examined, the results from that meta-analysis may be inconclusive.…”
Section: Carosella Et Al (2015)mentioning
confidence: 99%